2018
DOI: 10.3389/fimmu.2018.00359
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline Suppresses NADPH Oxidase-Dependent Neutrophil Extracellular Trap Formation and Promotes Apoptosis

Abstract: Tonicity of saline (NaCl) is important in regulating cellular functions and homeostasis. Hypertonic saline is administered to treat many inflammatory diseases, including cystic fibrosis. Excess neutrophil extracellular trap (NET) formation, or NETosis, is associated with many pathological conditions including chronic inflammation. Despite the known therapeutic benefits of hypertonic saline, its underlying mechanisms are not clearly understood. Therefore, we aimed to elucidate the effects of hypertonic saline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 77 publications
2
42
0
3
Order By: Relevance
“…Therefore, we wanted to determine whether the HS-increased antibacterial effects observed here similarly hinge on enhanced NO and/or ROS (reactive oxygen species) production. In line with a recent publication [33], HS treatment decreased ROS production in E. coliinfected MΦ (Figure 3(a)). In MΦ from mice deficient for the Cybb (cytochrome b 245 subunit of phagocyte NADPH oxidase [cybb -/-]), HS treatment similarly increased antibacterial activity (Figure 3(b)).…”
Section: Increased Antibacterial Activity Of Macrophages Under High Nsupporting
confidence: 92%
“…Therefore, we wanted to determine whether the HS-increased antibacterial effects observed here similarly hinge on enhanced NO and/or ROS (reactive oxygen species) production. In line with a recent publication [33], HS treatment decreased ROS production in E. coliinfected MΦ (Figure 3(a)). In MΦ from mice deficient for the Cybb (cytochrome b 245 subunit of phagocyte NADPH oxidase [cybb -/-]), HS treatment similarly increased antibacterial activity (Figure 3(b)).…”
Section: Increased Antibacterial Activity Of Macrophages Under High Nsupporting
confidence: 92%
“…Given the important role NETosis plays in CF inflammation, drugs that inhibit NETosis or inhibit the interaction of NETs with other immune cells and epithelial cells may have a significant impact on CF airway inflammation. Such speculation has been confirmed in recent laboratory studies that demonstrated that hypertonic saline suppressed NETosis and reactive oxygen species production induced by exposure to LPS, P aeruginosa and other triggers …”
Section: Cellular Contributions To the Cf Airway Inflammatory Responsementioning
confidence: 83%
“…Such speculation has been confirmed in recent laboratory studies that demonstrated that S36 | hypertonic saline suppressed NETosis and reactive oxygen species production induced by exposure to LPS, P aeruginosa and other triggers. 74…”
Section: Neutrophilsmentioning
confidence: 99%
“…Also, no real consensus yet exists about which medium to use for the storage of neutrophils prior to or during assessing NET formation in vitro, although the composition of the culture medium strongly influences the propensity to form NETs [153,154] (st. 80). Also, NET assays must be performed under controlled CO 2 /HCO 3 -/pH balance [155][156][157] (st. 81).…”
Section: Materials and Methods In Net-related Researchmentioning
confidence: 99%